Using Triadic Interview to Explore Complex Interactional-Based Phenomena - Margaret Hay Ping Suen; Amy Yin Man Chow; Yong Hao Ng (International Journal of Qualitative Methods)
Many qualitative studies are carried out by interviewing one participant. When understanding the dynamic interactions and consented conclusion of two or more participants is the research focus, single-participant interviews are not adequate as they can only provide a one-sided picture of the phenomenon. Dyadic interviews capture interactions between two participants. However, no reports of triadic interviews in research have been used by researchers with three participants and an interviewer. This article introduces this advanced triadic interview method. It explains and uncovers the process of applications from pre-planning to implementation. Examples of interviewing three participants including a patient, a family caregiver, and a healthcare professional are included to illustrate the dynamic interactions unfolded in the triadic interviews. The role of the interviewer, facilitation skills and analysis of the triadic interviewing method are also explained. The triadic interview is a viable data collection method for studying a phenomenon involving three participants. It has the advantage of accessing both individual and interactional level influences between three participants on individuals’ behaviours simultaneously.